Discrepancy Analysis of Authentic Assessment Implementation Based on Curriculum 2013 in EFL Classroom at SMA Negeri 1 Kuta Utara, Badung - Suastini, N.L.P. (Universitas Pendidikan Ganesha, 2018)
This study aimed at analyzing the discrepancy between the ideal authentic assessment implementation and the real implementation in a Senior High School EFL class at senior, and describing the teachers’ belief on authentic assessment. The study was conducted in SMAN 1 Kuta Utara, Badung. There are two research questions which become guidelines of this study: a) the extent of the discrepancy of authentic assessment implementation in EFL classroom of SMAN 1 Kuta Utara based on Curriculum2013; b) the EFL teachers’ belief on the authentic assessment based on Curriculum 2013. The research employed Discrepancy Evaluation Model by Provus modified by Marhaeni (2012). The data were collected through observation sheet, questionnaire and interview. The obtained data were analyzed using descriptive statistics of Ideal Theoretical Reference. The research found that in self-assessment, the discrepancy was big (77,22%); in performance assessment, the discrepancy was kecil (10.04%);in project assessment, the discrepancy was very big (5.5%), and in portfolio assessment, the discrepancy was big (66.26%). In general it can be concluded that the discrepancy in authentic assessment implementation in EFL classroom at SMAN 1 Kuta Utara was categorized as moderate (46.19%). In contrast with the finding of discrepancy of authentic assessment, the finding in teachers’ belief is positive (65.56%). These findings indicate that teachers’ belief are positive toward authentic assessment but they did not optimally implement authentic assessment.